Assessing the genetic integrity of sugarcane germplasm in the USDA-ARS National Plant Germplasm System collection using single-dose SNP markers - Park, Sunchung; Zhang, Dapeng; Ali, Gul Shad (Frontiers in Plant Science, 2024)
The World Collection of Sugarcane and Related Grasses, maintained at the USDA-ARS in Miami, FL, is one of the largest sugarcane germplasm repositories in the world. However, the genetic integrity of the Saccharum spp. germplasm in this collection has not been fully analyzed. In this study, we employed a single-dose SNP panel to genotype 901 sugarcane accessions, representing six Saccharum species and various hybrids. Our analysis uncovered a high rate of clone mislabeling in the collection. Specifically, we identified 86 groups of duplicates, characterized by identical SNP genotypes, which encompassed 211 accessions (23% of the total clones), while 135 groups, constituting 471 clones (52% of the total), exhibited near-identical genotypes. In addition, twentyseven homonymous groups were detected, which shared the same clone name but differed in SNP genotypes. Hierarchical analysis of population structure partitioned the Saccharum germplasm into five clusters, corresponding to S. barberi, S. sinense, S. officinarum, S. spontaneum and S. robustum/S. edule. An assignment test, based on the five Saccharum species, enabled correcting 141 instances of mislabeled species memberships and inaccuracies. Moreover, we clarified the species membership and parentage of 298 clones that had ambiguous passport records (e.g., 'Saccharum spp', 'unknown', and 'hybrid'). Population structure and genetic diversity in these five species were further supported by Principal Coordinate Analysis and neighbor-joining clustering analysis. Analysis of Molecular Variance revealed that within-species genetic variations accounted for 85% of the total molecular variance, with the remaining 15% attributed to among-species genetic variations.